2006
DOI: 10.1128/aac.01641-05
|View full text |Cite
|
Sign up to set email alerts
|

Novel Real-Time Monitoring System for Human Cytomegalovirus- Infected Cells In Vitro That Uses a Green Fluorescent Protein-PML-Expressing Cell Line

Abstract: Promyelocytic leukemia (PML) bodies are discrete nuclear foci that are intimately associated with many DNA viruses. In human cytomegalovirus (HCMV) infection, the IE1 (for "immediate-early 1") protein has a marked effect on PML bodies via de-SUMOylation of PML protein. Here, we report a novel real-time monitoring system for HCMV-infected cells using a newly established cell line (SE/15) that stably expresses green fluorescent protein (GFP)-PML protein. In SE/15 cells, HCMV infection causes specific and efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Unlike other assays, including PRA, which are based on measuring the spread of progeny virus in cell culture (11,18,22,23,35), our FIR assay allows the determination of EC 50 s from single-cycle virus replication. This accelerates testing and allows indirect evaluation of polymerase activity at higher MOIs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike other assays, including PRA, which are based on measuring the spread of progeny virus in cell culture (11,18,22,23,35), our FIR assay allows the determination of EC 50 s from single-cycle virus replication. This accelerates testing and allows indirect evaluation of polymerase activity at higher MOIs.…”
Section: Discussionmentioning
confidence: 99%
“…Many efforts have been made to develop new assays which are easier to perform and allow for better standardization. Some groups have generated reporter cell lines that allow determination of IC 50 s by measuring HCMV spread in cell culture, reflected by luciferase activity (18) or green fluorescent protein (GFP) intensity (35). Other assays are based on recombinant viruses expressing reporter proteins, such as GFP (23), enhanced yellow fluorescent protein (12; Sarah Straschewski and Michael Winkler, personal communication), or secreted alkaline phosphatase (11).…”
mentioning
confidence: 99%
“…We and others generated reporter cell lines for herpesviruses, including herpes simplex virus, B virus, HHV-8, and VZV (7,17,34,42,47). Two reporter cell lines for HCMV that depend on the activation of the UL54 (DNA polymerase) promoter were also published previously (13,45). However, since our transient-transfection experiments in this study and genomewide DNA microarray analyses (8) clearly demonstrated that the TRL4 promoter is severalfold stronger than the UL54 promoter, our cell line may have an advantage in terms of sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…The basic strategy is to stably introduce genetic elements into a cell in such a way that when a particular virus enters in the cell, a virus-specific event that results in the production of an easily measurable enzyme is triggered (Olivo, 1996;Leland and Ginocchio, 2007). Cell lines expressing reporter genes inducible upon viral infection have shown to be both sensitive and specific (Olivo, 1996;Lee et al, 2004;Lutz et al, 2005;Wang et al, 2006;Ueno et al, 2006;Wu et al, 2007;Fukui et al, 2008;Li et al, 2009;Iro et al, 2009;Hossain et al, 2010;Levy et al, 2010). These reporter cells exploit the specificity of viral infection in combination with the extreme sensitivity of reporter proteins such as luciferase, chloramphenicol acetyltransferase (CAT), LacZ (b-D-galactosidase), green fluorescence protein (GFP) or secreted alkaline phosphatase (SEAP).…”
Section: Introductionmentioning
confidence: 99%